Electrical Properties of Carbon Nanotube Based Fibers and Their Future Use in Electrical Wiring. (17th March 2014) - Lekawa‐Raus, Agnieszka; Patmore, Jeff; Kurzepa, Lukasz; Bulmer, John; Koziol, Krzysztof
<x xml:space="preserve">Abstract</x> The production of continuous fibers made purely of carbon nanotubes has paved the way for new macro‐scale applications which utilize the superior properties of individual carbon nanotubes. These wire‐like macroscopic assemblies of carbon nanotubes were recognized to have a potential to be used in electrical wiring. Carbon nanotube wiring may be extremely light and mechanically stronger and more efficient in transferring high frequency signals than any conventional conducting material, being cost‐effective simultaneously. However, transfer of the unique properties of individual CNTs to the macro‐scale proves to be quite challenging. This Feature Article gives an overview of the potential of using carbon nanotube fibers as next generation wiring, state of the art developments in this field, and goals to be achieved before carbon nanotubes may be transformed into competitive products.